Cognitivism Theory and Its Application in TechnologyBased Islamic Religious Education (PAI) Learning - Mamluatun Ni'mah; Muhammad Hafil Mangkudilaga; Rifka Diana Sosilowati (CV Kalimasada Group, 2026)
Purpose – This study analyzes how cognitivism theory—particularly the ideas of Jean Piaget and Jerome Bruner—together with the Cognitive Theory of Multimedia Learning (CTML), can inform the design of technology-based Islamic Religious Education (PAI) learning, and proposes an integrative framework that balances cognitive, affective, and spiritual dimensions. Design/Methodology/Approach – The study employs a qualitative library research approach. Sources were purposively selected from reputable books, journals, and articles published between 2015 and 2025 using defined inclusion and exclusion criteria, and were analyzed thematically. Conceptual triangulation across Western psychology, Islamic pedagogy, and multimedia-learning research was used to strengthen the credibility of the synthesis. Findings – Cognitive development theory and CTML jointly provide a sound basis for designing concrete digital mediators that bridge the “abstraction gap” in PAI while controlling cognitive load. However, cognitive efficiency alone is insufficient: the internalization of faith requires the affective–spiritual domain to be cultivated through reflection, worship habits, and the teacher’s moral example. These relationships are summarized in a proposed integrative framework. Originality/Value – The study contributes an explicit, framework-based integration of cognitivism, CTML, and Islamic pedagogy for technology-based PAI—positioning technology as a wasilah (medium) rather than a ghayah (goal)—and offers practical and research implications for holistic religious learning